2021
DOI: 10.17344/acsi.2021.6836
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Symmetry: Measuring the Contribution of Virtual and Concrete Models for Students with Different Spatial Abilities

Abstract: Virtual and concrete models have been of interest in chemistry teaching to improve students’ understanding of a three-dimensional representation of chemical concepts such as symmetry. This study aims to determine the effectiveness of using concrete and virtual models on students’ understanding of symmetry. Students’ understanding was also explored in light of their spatial ability. The study was conducted using a quasi-experimental design with 62 students as participants. Two different instruments, spatial abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The topic is used to understand solid-state chemistry, crystallography, stereochemistry, and quantum chemistry. (Achuthan et al, 2018;Antonoglou et al, 2011;Cass et al, 2005;Fuchigami et al, 2016;Kang & Kim, 2021;Niece, 2019;Schiltz & Oliver-Hoyo, 2012;Thayban et al, 2020Thayban et al, , 2021. By knowing the symmetry operation, the polarity and chirality of a molecule can be predicted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic is used to understand solid-state chemistry, crystallography, stereochemistry, and quantum chemistry. (Achuthan et al, 2018;Antonoglou et al, 2011;Cass et al, 2005;Fuchigami et al, 2016;Kang & Kim, 2021;Niece, 2019;Schiltz & Oliver-Hoyo, 2012;Thayban et al, 2020Thayban et al, , 2021. By knowing the symmetry operation, the polarity and chirality of a molecule can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Second, manipulating representations of three-dimensional objects in space (Tuvi-Arad & Gorsky, 2007). These tasks can be done correctly if students have good spatial visualisation, spatial orientation, and spatial relations skills (Achuthan et al, 2018;Al-Balushi & Al-Hajri, 2014;Kang & Kim, 2021;Thayban et al, 2021;Tuvi-Arad & Gorsky, 2007). Spatial visualisation is the ability that allows one to correctly interpret a two-dimensional representation of a three-dimensional object's shape and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been published in many journals and international proceedings, including highly reputable journals such as science education, chemistry education research and practice and journal of chemical education. Thayban et al (2021) described the role of virtual and concrete models in symmetry teaching and revealed that the virtual model demonstrated a higher contribution than the concrete model. 2D representation influenced students' success in translating from one representation to another in organic chemistry courses (Olimpo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…An ability to understand the 3D structure of a molecule and mentally imagine its behaviour is known as spatial ability [15], [16]. Lohman [9] defines spatial ability as generating, storing, and manipulating abstract visual images.…”
Section: Introductionmentioning
confidence: 99%
“…3D molecular shape modelling can assist students in developing their spatial abilities [28]. Another study employing a 3D molecular model improved chemistry students' understanding of symmetry [15]. Modelling in chemistry has been applied in several areas, including chemical bonding, symmetry, stereochemistry, and other topics [16].…”
Section: Introductionmentioning
confidence: 99%